What to do with device-detected atrial high-rate episodes: Summary of the evidences - KEPEZ, ALPER (My University, 2021)
Cardiac implanted electronic devices (CIEDs), that perform atrial sensing via an atrial electrode, commonly detect self-terminating atrial arrhythmias. Nomenclature of these arrhythmias is defined as atrial high-rate episodes (AHREs) and subclinical atrial fibrillation (SCAF). We have provided a comprehensive summation of the trials regarding the incidence and adverse outcomes of AHREs. The reported incidence of AHRE varies considerably (approximately 10% to %70) between studies depending on the definition of AHRE, duration of follow-up and the clinical profile of the population. There is increasing evidence related with the association between AHREs' and stroke and/or systemic embolism. However, risk of stroke and/or systemic embolism seems to be less than the risk associated with clinical AF. There is still lack of sufficient evidence related with oral anticoagulation (OAC) in patients with AHRE to reduce thromboembolic risk. Although, the strongest association of OAC treatment with reduction in stroke has been reported to be observed among patients with device detected SCAF episodes of >24 hours; it is still questionable whether AHRE is a direct cause of thromboembolic event or just a marker of increased risk. Results of ongoing randomized clinical trials (NOAH-AFNET 6 and ARTESIA) will provide robust evidence on effect of OAC therapy on AHREs. This article is protected by copyright. All rights reserved.
Keywords: atrial fibrillation; stroke; atrial high-rate episodes; oral anticoagulation; systemic embolism